Dynamic assessment of a frp suspension footbridge - Stratford, Tim J.; Chryssanthopoulos, Marios K.; Votsis, Renos (My University, 2009)
In the past decade, the vibration serviceability of slender footbridges has become the subject of serious investigation. Despite the advantages that FRP materials offer in bridge engineering such as higher strength-to-weight ratio and ease of installation, their use in the construction of slender footbridges has raised concerns with regard to their dynamic response, due to the reduced mass and stiffness of these materials compared with their conventional counterparts. In this paper, the dynamic assessment of a FRP suspension footbridge (the Wilcott footbridge) is described. This is performed using dynamic field testing supported by finite element (FE) modelling: the field testing on the bridge produced values for frequencies, mode shapes and damping which were consequently used to calibrate the FE model. Using the calibrated FE model it was shown that the influence of semistructural or non-structural elements, such as parapets, on the dynamic properties of the structure can be significant. The dynamic response of the structure due to human excitation was also measured during the test. The results confirmed that suspension footbridges built from FRP materials are susceptible to vibrations induced by pedestrians. The response levels of the investigated bridge are lower than the threshold levels specified in the relevant code of practice.
Keywords: Finite element method; Strength of materials